Healthcare utilization during the first two waves of the COVID-19 epidemic in South Africa: A cross-sectional household survey. - Nicole Wolter; Stefano Tempia; Anne von Gottberg; Jinal N Bhiman; Sibongile Walaza; Jackie Kleynhans; Jocelyn Moyes; Sue Aitken; Sarah Magni; Jessica Yun; Tamika Fellows; Tetelo Makamadi; et al. (PLoS ONE)
Healthcare utilization surveys contextualize facility-based surveillance data for burden estimates. We describe healthcare utilization in the catchment areas for sentinel site healthcare facilities during the first year of the COVID-19 pandemic. We conducted a cross-sectional healthcare utilization survey in households in three communities from three provinces (KwaZulu-Natal, Western Cape and North West). Field workers administered structured questionnaires electronically with the household members reporting influenza-like illness (ILI) in the past 30 days or severe respiratory illness (SRI) since March 2020. Multivariable logistic regression was used to identify factors associated with healthcare utilization among individuals that reported illness. From November 2020 through April 2021, we enrolled 5804 households and 23,003 individuals. Any respiratory illness was reported by 1.6% of individuals; 0.7% reported ILI only, 0.8% reported SRI only, and 0.1% reported both ILI and SRI. Any form of medical care was sought by 40.8% (95% CI 32.9% - 49.6%) and 71.3% (95% CI 63.2% - 78.6%) of individuals with ILI and SRI, respectively. On multivariable analysis, respiratory illness was more likely to be medically attended for individuals at the Pietermaritzburg site (aOR 3.2, 95% CI 1.1-9.5, compared to Klerksdorp), that were underweight (aOR 11.5, 95% CI 1.5-90.2, compared to normal weight), with underlying illness (aOR 3.2, 95%CI 1.2-8.5), that experienced severe illness (aOR 4.8, 95% CI 1.6-14.3) and those with symptom duration of ≥10 days (aOR 7.9, 95% CI 2.1-30.2, compared to <5 days). Less than half of ILI episodes and only 71% of SRI episodes were medically attended during the first two COVID-19 waves in South Africa. Facility-based data may underestimate disease burden during the COVID-19 pandemic.